Bone Loss in Ankylosing Spondylitis: A Controlled Study - Original Investigation - Nurdan Paker; Demet Tekdöş; Metin Erbil; Derya Soy; Ayşenur Bardak (Galenos Yayinevi, 2006)
Osteoporosis is common in ankylosing spondylitis (AS), which is a chronic inflammatory rheumatic disease.The aim of this study was to assess the bone loss and the effects of disease activity on bone mineral density in patients with AS. Thirty-three (29 men ,4 women ) patients with AS were included in the study. All of the patients were evaluated as their age, sex, height, weight, history, physical examination, laboratory and AP-lateral thoracic and lumbar vertebrae radiographic findings. Control group was consisted of 35 (31 men 4 women) age and sex-matched healthy person. Mean age and disease duration of the patient group were 43.2 ± 9.9 and 13.18 ± 10.6 years, respectively. Bone mineral density (BMD) was measured by dual energy x-ray absorptiometry (DXA) at lumbar spine and proximal femur regions. BMD did not show statistically significant difference at lumbar region between two groups. However BMD values were 10% lower at femur neck in patient group than controls. The rate of osteopenia and osteoporosis was 42.8 % at the femur neck region in the patient group and 22.8 % in the control group. BMD values at femur neck correlated with age and disease duration. There was no correlation between BMD and BASDAI and BASMI, BASFI, BASGI scores. In conclusion, bone loss is common in AS. Ligament calcification and syndesmophytes may lead to higher BMD values at lumbar region in AS .Thus proximal femur BMD is valuable in the patients with long disease duration. Disease activity has no negative effect on bone density in our study. (Osteoporoz Dünyasından 2006;12:81-3)